Hypospadias and Increased Risk for Psychiatric Symptoms in Both Childhood and Adolescence: A Literature Review - Jin, Tingting; Wu, Weizhou; Shen, Maolei; Feng, Haiya; Wang, Ya; Liu, Shixiong; Li, Xin; Zhao, Shankun (Frontiers in Psychiatry, 2022)
Hypospadias is one of the most frequent congenital malformations in boys. Due to abnormal appearance in the penis with abnormal urination and erection, patients with hypospadias were vulnerable to suffering from stress and psychological difficulties. The present study aims to summarize all the current evidence of the association between hypospadias and the risk of psychiatric disorders by a comprehensive review. Ten clinical studies were identified in the four electronic databases. A total of 473,187 participants were involved, while 9,868 were hypospadiac patients and 463,319 were normal controls. The age at criterion operation of hypospadias ranged from 20.4 months to 21.5 years. Six out of ten (6/10, 60%) included studies suggested that patients with hypospadias have a significantly higher risk of psychosocial disorders (all P<0.05). Specific types of psychological disorders included depression, anxiety, shyness, timidness, isolation, fear of ridicule, attention-deficit hyperactivity, autism spectrum, behavioral/emotional disorders, temper tantrums, emotionality, affective, and suicidal. Based on this review, psychiatric illnesses are frequently detected in hypospadiac patients’ childhood, thus proper psychological guidance and early interventions from physicians, nurses, and patients may help these children to grow into less affected men.